Nivel de conocimientos de los cuidadores de pacientes con pie diabético y su relación con futuras complicaciones en el Hospital General Liborio Panchana Sotomayor. Periodo mayo - septiembre 2019. - Jiménez Macías, Johanna Mishell (2019)
Introduction: The complications produced from type 2 diabetes mellitus can be microvascular and macrovascular. The first are ocular lesions such as retinopathy, renal lesions (nephropathy) and nerve lesions that cause male sexual impotence and diabetic foot. Objective: To determine the relationship between the level of knowledge of caregivers of patients with diabetic foot and the prevention of future complications in people with type 2 diabetes mellitus who attend the General Hospital Liborio Panchana Sotomayor during the period from May to September 2019. Methodology: Field study, exploratory, descriptive, cross-sectional, with a qualitative-quantitative approach. An intentional non-probabilistic sampling was carried out according to inclusion and exclusion criteria, being constituted by 35 patients who presented complications derived from diabetic foot injuries. Results: From the total sample, it was evidenced that most of the sample (27/35), represented by 77.14% of the total caregivers, have experience performing the caregiver activity. It was possible to verify that the caregivers do know (27/35) the vast majority of the complications that can lead to the appearance or poor care of an ulceration in their patient and that on a large scale they can lead to amputation and even death. Conclusions: Regarding the level of knowledge, the vast majority 51.43%, stated that their knowledge was obtained through instructions and talks provided by medical and nursing staff each time they attended the consultations.